(untitled) (Homoeopathy for All, 2025)
Globally, pneumonia is leading cause of morbidity & mortality in children’s younger than the age up to 5 years. • Although the majority of deaths attributed to pneumonia in children are mostly in the developing world, the burden of disease is substantial & there is significant health care associated costs related to pneumonia in developed world. • Pneumonia can be caused by viruses, bacteria or fungi. • Pneumonia can be prevented by immunization, adequate nutrition & by addressing environmental factors. • Pneumonia is the form of acute respiratory infection that affects the lungs • Lungs are made up of small sacs called alveoli which filled with pus & fluid which make breathing painful & limits oxygen intake • Pneumonia killed 808,694 childrens under the age of 5 in 2017, and a child dies of pneumonia every 43 seconds.